Influence of petal parameters on the electromagnetic force driving the arc in RMF type vacuum interrupters. Issue 7 (18th May 2018) - Bhat, Rahul; Kulkarni, Shrikrishna V.
Abstract : The SWASTIK type radial magnetic field (RMF) contact design is widely used in vacuum interrupters. The mutually perpendicular petal limbs are a unique feature of this contact design. The focus of this work is to relate the Lorentz force acting on the arc with petal dimensions through closed‐form expressions. Considering the petal limbs as equivalent to finite current carrying conductors, analytical equations are derived to compute the magnetic flux density at any point in space. The results are verified by using finite‐element method (FEM) simulations of rail electrodes. The expressions are then used to compute the Lorentz force on the arc in SWASTIK contacts. The analytical predictions are compared with three‐dimensional FEM simulations of a CAD model of the contacts. Applicability of the analytical results is investigated in the context of parametric variation of the radius, length and position of the arc and temporal variation of the contact current. The present work can be used in the first iteration of contact petal design. It is also applicable for the design of rail gun geometries.